Oral Treatments With the TrkB Ligand Prodrug, R13, Promote Enhanced Axon Regeneration Following Peripheral Nerve Injury - English, Arthur W.; Carrasco, Dario; Hoffman, Dustin; Isaacson, Robin; Kang, Seong Su; Khan, Samia; Liu, Xia; Ye, Keqiang (Frontiers in Cellular Neuroscience, 2022)
Axon regeneration after peripheral nerve injury is slow and inefficient, leading to generally poor functional recovery. Activity-dependent experimental therapies that increase expression of brain-derived neurotrophic factor (BDNF) and its TrkB receptors enhance regeneration, suggesting that treatments with BDNF might also be effective. However, recombinant human BDNF (rhBDNF), as well as 7,8-dihydroxyflavone (7,8-DHF), a small molecular BDNF mimetic, may have limited treatment applications because of their modest oral bioavailability and pharmacokinetic profile. R13 is a 7,8-DHF prodrug. Upon oral administration, it is converted in the liver to 7,8-DHF. In immunoblots from tissues at the site of nerve injury, a single oral treatment with R13 to mice following sciatic nerve transection and repair produced a rapid and prolonged increase in immunoreactivity to phosphorylated TrkB, prolonged phosphorylation of mitogen activated protein kinase (MAPK/Erk1/2), and a rapid but transient increase in phosphorylated AKT (protein kinase B). Intramuscular injections of fluorescent retrograde tracers into the gastrocnemius and tibialis anterior muscles 4 weeks after nerve injury resulted in significantly greater numbers of labeled motoneurons and dorsal root ganglion neurons in R13-treated mice than in vehicle-treated controls. Direct electromyographic (EMG) responses (M waves) were significantly larger in R13-treated mice 4 weeks after injury than vehicle-treated controls or mice treated with oral 7,8-DHF. Oral treatments with the prodrug, R13, are a potent therapy for stimulating axon regeneration and functional recovery after peripheral nerve injury.